2023
DOI: 10.1186/s12889-023-16733-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the COVID-19 lockdowns on motor skill development of 6- and 7-year old children in the Netherlands: a longitudinal study

Anne R. den Uil,
Hemke van Doorn,
Mandy Schweitzer
et al.

Abstract: Background The closing of schools and sports clubs during the COVID-19 lockdown raised questions about the possible impact on children’s motor skill development. Therefore, we compared motor skill development over a one-year period among four different cohorts of primary school children of which two experienced no lockdowns during the study period (control cohorts) and two cohorts experienced one or two lockdowns during the study period (lockdown cohorts). Methods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Studies performed on MCD-aged children showed that the COVID-19 pandemic resulted in decreased motor skills due to children's activities at home, such as increased sleeping habits, increased eating habits, and increased screen time [47][48][49]. However, a recently published study by den Uil and colleagues [50] showed the COVID-19 lockdowns in the Netherlands did not negatively affect motor skill development of MCD children. Therefore, more longitudinal research is needed to explore the long-term effects of the COVD-19 pandemic on MC development.…”
Section: Discussionmentioning
confidence: 96%
“…Studies performed on MCD-aged children showed that the COVID-19 pandemic resulted in decreased motor skills due to children's activities at home, such as increased sleeping habits, increased eating habits, and increased screen time [47][48][49]. However, a recently published study by den Uil and colleagues [50] showed the COVID-19 lockdowns in the Netherlands did not negatively affect motor skill development of MCD children. Therefore, more longitudinal research is needed to explore the long-term effects of the COVD-19 pandemic on MC development.…”
Section: Discussionmentioning
confidence: 96%